Peran Kepuasan Pelanggan Memoderasi Pengaruh Kualitas Pelayanan dan Pengalaman Pelanggan Terhadap Loyalitas Pelanggan E-Commerce pada Generasi Z di Jabodetabek - Nurjanah, Anisa; Sriminarti, Nurul (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
The purpose of this study was to determine the role of customer satisfaction in moderating the influence of service quality and customer experience on customer loyalty. This study uses a survey method with a questionnaire as its instrument. The respondents of this study were 160 respondents who used e-commerce in the Jabodetabek area. The sampling process used a nonprobability sampling technique using a quantitative approach that was associative using primary data. The method used was the PLS-SEM method with WARP-PLS 7.0 as its software. These results indicate that Service Quality has a positive and significant effect on Customer Loyalty, Customer Experience has a positive and significant effect on Customer Loyalty, Customer Satisfaction moderates the relationship between Service Quality and Customer Loyalty significantly, although with a small moderation contribution, thus the customer satisfaction variable can be said to be a Quasi Moderation. And Customer satisfaction is unable to moderate Customer Experience on Customer Loyalty but is significant when used as a direct variable, so from this the customer satisfaction variable can be called Pure Moderation.